Applications of surficial mapping to forest management in New Brunswick - Pronk, A.; Ruitenberg, A. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1991)
Joint investigations of the Geological Surveys (G.S.B.) and Timber Management (T.M.B.) branches of the New Brunswick Department of Natural Resources and Energy during the past ten years have demonstrated a well-defined relationship between forest productivity for different species with several geologic and climatic parameters. A method referred to as regolith mapping developed by the G.S.B. has enabled theT.M.B. to evaluate these geologic parameters in forest productivity. The growth curves for certain tree species on soils that formed on different regolith systems are discussed. The results of this work have been incorporated in long-term forest management plans.